Areas Of Significance For Advancing Economic Development - Anna Caroline Gwenevieve (Dynamics Social : International Journal of Social Sciences and Communication, 2025)
This study explores areas that are important in supporting economic growth. By analyzing the key factors that influence economic development, this research provides an in-depth understanding of the aspects that need to be considered in efforts to improve a country's economic welfare. Through an examination of areas such as infrastructure, education, innovation, public policy, and the industrial sector, this study highlights the importance of cross-sector collaboration and holistic strategies in stimulating sustainable economic growth.